ANALISIS PENGELOLAAN LIMBAH MEDIS DI RUMAH SAKIT UMUM DAERAH (RSUD) GUNUNGTUA KABUPATEN PADANG LAWAS UTARA PROPINSI SUMATERA UTARA - Ayu Ade Fatma Dewi Sirait; Aras Mulyadi; Elda Nazriati (Program Pascasarjana Universitas Riau, 2015)
ABSTRACTMedical waste derived from public hospital is of a serious problem enviromentmentally, therefore it need to be managed properly starting from collection of waste until the process of destruction, coresponding to the regulation of the ministry of health, the present study aimed at assessing the management of waste of Gunungtua Public Hospital, a field survey and observation was conducted during September-October 2014, in Padang Lawas Utara District. Eleven informants were interviewed. Apparently, waste processing facilities as wel as infrastructures of Gunungtua Public Hospital has not build up completely, as a resuld the waste processing has well performed in relation to the goverment regulation in waste standard. Full support from the local goverment did not met the need for whole facilities. SWOT analysis suggested that four cells strategies, wich of the eight strategies.